Big size R-Fe-B sintered magnets and their manufacturing method and applications

By using a diffusion portion with alternating M and RH layers and a tailored heat treatment process, the method effectively addresses the challenge of diffusing heavy rare earth elements in big size sintered magnets, resulting in improved coercivity uniformity and cost reduction.

JP2025507780AActive Publication Date: 2025-03-21YANTAI ZHENGHAI MAGNETIC MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024550867
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-30
Filing Date
2023-07-18
Publication Date
2025-03-21
Estimated Expiration
2043-07-18

AI Technical Summary

Technical Problem

Current big size sintered magnets face challenges in diffusing heavy rare earth elements effectively due to increased thickness, leading to uneven coercive forces and high production costs.

Method used

The method involves arranging a diffusion portion with alternating M and RH layers on the surface of the magnet billet, followed by a diffusion heat treatment process that includes DW and ST heat treatments, to adjust the heavy rare earth concentration and enhance diffusion depth.

Benefits of technology

This approach achieves more uniform internal coercivity of the sintered magnet, reduces the consumption of heavy rare earth elements, and lowers production costs by optimizing the diffusion process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507780000001_ABST
    Figure 2025507780000001_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of rare earth permanent magnet materials and discloses a large-sized R-Fe-B sintered magnet and its manufacturing method and application. The thickness of the R-Fe-B sintered magnet in the orientation direction of the present invention is more than 10 mm, and any one of the cross sections along the orientation direction is a diffusion cross section area, and the side of the diffusion cross section area close to the outer surface of the R-Fe-B sintered magnet is the diffusion cross section area surface, and the difference in coercivity between the diffusion cross section area surface and the point 5 mm away from the diffusion cross section area surface is ΔH, and ΔH≦50 kA / m. Compared with the conventional grain boundary diffusion method, the manufacturing method of the present invention solves the problems that the current large-sized sintered magnet is too thick, which makes it difficult for heavy rare earth to diffuse into the magnet, the difference in coercivity between the magnet surface and the inside after diffusion treatment is large, and the heavy rare earth is consumed in large amounts by diffusion and the diffusion period is long.
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] (Technical field) This application claims priority to a prior application filed with the State Intellectual Property Office of the People's Republic of China on December 30, 2022, bearing patent application number 202211734983.2 and entitled "Big-size R-Fe-B sintered magnet and its manufacturing method and application," which is incorporated herein by reference in its entirety.

[0002] The present invention relates to a large-size R-Fe-B sintered magnet and its manufacturing method and application, which belong to the field of rare earth permanent magnet materials.

[0003] (Background technology) Under the current global trend of low-carbon economy and energy revolution, countries are increasingly paying attention to green energy, and reducing the combustion of fossil energy and accelerating the development and use of renewable energy has become the direction of action for countries around the world. Wind power generation is widely used around the world as a technologically mature and environmentally friendly renewable energy. Wind power generation, along with traditional hydroelectric power generation, has become the most widely used renewable energy. Current wind power generation technology has been gradually improved, and the installed capacity of onshore and offshore wind power generation has been increasing year by year. In wind turbines, both use neodymium-iron-boron sintered permanent magnets, accounting for nearly one-third of the cost of the generator. At the same time, with the increase in size of construction machinery, the demand for neodymium-iron-boron permanent magnets for motors is also increasing, and the size of the magnets required in the above fields is relatively large, and the thickness of the products is basically 10 mm or more.

[0004] As the amount of rare earth permanent magnet materials used increases, the price of heavy rare earth materials has risen sharply due to their scarcity, and reducing the amount of heavy rare earth materials used in large-size sintered magnets is an issue that must be resolved immediately. In the field of sintered NdFeB, the heavy rare earth elements Dy and Tb arranged on the magnet surface are diffused into the magnet along the grain boundaries, realizing mass production using the grain boundary diffusion method that refines the microstructure. By improving the coercive force of sintered NdFeB and reducing the magnetic exchange coupling action of the grain boundaries, the grain boundaries are magnetically hardened, and the coercive force of the magnet is greatly improved under the premise that the remanence of the magnet is hardly reduced. Grain boundary diffusion is a method in which heavy rare earth elements are arranged on the magnet surface, and the grain boundary phase becomes molten under high temperature conditions, and the concentration difference between the heavy rare earth elements on the magnet surface and inside is used as a diffusion force. For magnets with a small thickness, heavy rare earths diffuse easily to the center of the magnet, and the distribution of the diffused heavy rare earths at the grain boundaries on the magnet surface and inside the magnet is uniform. However, as the magnet becomes thicker, the heavy rare earths diffuse less easily into the magnet's interior, and simply increasing the amount of heavy rare earth placed on the magnet surface results in a rapid rise in product costs. Therefore, the development of grain boundary diffusion processes and methods for large-sized sintered magnets has relatively high application value.

[0005] (Summary of the invention) The present invention provides a sintered R-Fe-B magnet, the thickness of which in the orientation direction is 10 mm or more, any one cross section along the orientation direction is a diffusion cross-sectional area, the side of the diffusion cross-sectional area close to the outer surface of the R-Fe-B sintered magnet is the diffusion cross-sectional area surface, the difference in coercivity between the diffusion cross-sectional area surface and a point 5 mm away from the diffusion cross-sectional area surface is ΔH, and ΔH≦50 kA / m. In the present invention, the diffusion cross-sectional area surface is preferably a portion 1 mm away from the outer surface of the R-Fe-B sintered magnet.

[0006] According to an embodiment of the present invention, ΔH is, for example, 45 kA / m or less, such as 42 kA / m, 38 kA / m.

[0007] According to an embodiment of the present invention, the thickness in the orientation direction is, for example, 10 mm to 20 mm, for example, 11 mm, 15 mm.

[0008] According to an embodiment of the present invention, the raw materials of the R-Fe-B sintered magnet include R, B, Fe, and M, among which: The mass content of R is 27 to 34 wt%, preferably 29 to 32 wt%, for example, 30.2 wt%.

[0009] The mass content of M is 0 to 5 wt%, preferably 0 to 3 wt%, for example, 2 wt%.

[0010] According to an embodiment of the present invention, R is at least one selected from the rare earth elements Nd, Pr, Tb, Dy, Gd, Ho.

[0011] According to an embodiment of the present invention, M is at least one selected from Ti, V, Cr, Mn, Co, Ga, Cu, Si, Al, Zr, Nb, W, Mo.

[0012] The present invention further provides a method for producing the above-mentioned R-Fe-B sintered magnet, the method comprising the steps of: (1) producing a billet of R-Fe-B magnet having a thickness of ≧10 mm; (2) Arrangement of a diffusion section: arranging a diffusion section on at least two surfaces in the orientation direction of the billet obtained in step (1), the diffusion section including at least one RH layer and one M layer, the M layer being in direct contact with the billet surface, and at least one M layer being spaced between the RH layer and the billet; (3) Diffusion Heat Treatment: The billet on which the diffusion layer is disposed in step (2) is subjected to a diffusion heat treatment to obtain the R—Fe—B sintered magnet.

[0013] According to an embodiment of the present invention, in step (1), the R-Fe-B magnet billet is obtained by preparing the raw material of the R-Fe-B sintered magnet by a method known in the art, which is not particularly limited in the present invention.

[0014] According to an embodiment of the present invention, in step (2), the diffusion section has RH layers and M layers alternately arranged, and at least one M layer is separated between the RH layer and the billet, the number of the RH layers is 1 to 3, and the number of the M layers is 1 to 3.

[0015] According to an exemplary embodiment of the present invention, the diffusion portion includes one M layer and one RH layer.

[0016] According to an exemplary embodiment of the present invention, the diffusion section includes two M layers and two RH layers, which are arranged in the order of a first M layer, a first RH layer, a second M layer, and a second RH layer from the surface of the billet. Preferably, the first M layer and the second M layer may be either homologous or different. Preferably, the first RH layer and the second RH layer may be either homologous or different.

[0017] According to an embodiment of the present invention, in the diffusion portion, the thickness of each RH layer is 1 μm to 70 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, or 50 μm.

[0018] According to an embodiment of the present invention, the method for preparing the RH layer specifically includes disposing an RH slurry on two surfaces in the orientation direction of the billet, and then drying to obtain the RH layer.

[0019] According to an embodiment of the present invention, the RH slurry includes a heavy rare earth element, an organic solid, and a solvent.

[0020] According to an embodiment of the present invention, in the RH slurry, the mass ratio of the heavy rare earth element, the organic solid, and the solvent is (40-70):(0.5-12):(0-50), for example, 62:8:30 or 60:8:32.

[0021] According to an embodiment of the present invention, the heavy rare earth element includes at least one of dysprosium metal, terbium metal, dysprosium hydride, terbium hydride, dysprosium fluoride, terbium fluoride, dysprosium oxide, and terbium oxide.

[0022] According to an embodiment of the present invention, the organic solid is at least one selected from a rosin-modified alkyd resin, a thermoplastic phenolic resin, a urea resin, and a polyvinyl butyral.

[0023] According to an embodiment of the present invention, the solvent is at least one selected from an alcohol-based solvent (e.g., methanol, ethanol), an ether-based solvent (e.g., ethyl ether), and an aromatic hydrocarbon-based solvent (e.g., benzene), and the solvent is preferably ethanol.

[0024] According to an embodiment of the present invention, in the diffusion section, the thickness of each M layer is smaller than 20 μm and larger than 0.1 μm, preferably equal to or smaller than 10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm.

[0025] According to an embodiment of the present invention, in the diffusion section, the thickness ratio of each RH layer to each M layer is (1 to 70):(0.1 to 20), for example, 50:3, 40:3, 35:3, 40:2, or 35:2.

[0026] According to an embodiment of the present invention, the manufacturing method of the M layer specifically includes disposing a slurry containing M powder on two surfaces in the orientation direction of the billet, and then drying to obtain the M layer.

[0027] According to an embodiment of the present invention, the M powder-containing slurry includes M powder, an organic solid, and a solvent.

[0028] According to an embodiment of the present invention, in the M powder-containing slurry, the mass ratio of M powder, organic solid, and solvent is (20-70):(1-10):(0-50), for example, 60:5:35, 55:5:40.

[0029] According to an embodiment of the present invention, the M powder includes at least one of graphite powder, titanium powder, zirconium powder, molybdenum powder, tungsten powder, titanium oxide, zirconium oxide, molybdenum oxide, and tungsten oxide, and the content of oxygen element in the M powder is less than 3%, preferably less than 1%.

[0030] According to an embodiment of the present invention, the M powder includes powders having a particle size of less than 5 μm, of which the powders having a particle size between 0.5 μm and 1.8 μm account for 50% or more, preferably more than 65%, of the total mass of the powder.

[0031] Generally, as the diffusion progresses, the heavy rare earth on the magnet surface is consumed, and as the amount of heavy rare earth on the magnet surface decreases, the concentration difference formed also becomes smaller, and the heavy rare earth cannot diffuse into the magnet interior (for example, the part with a thickness of 5 mm or more in the orientation direction). In this case, the amount of heavy rare earth used on the magnet surface and the thickness of the RH layer placed on the magnet increase obviously with the increase in thickness, while the diffusion path becomes significantly longer with the increase in magnet orientation thickness. The conventional method for diffusing large-sized magnets extends the diffusion time, but the effect of increasing the thickness is becoming less and less obvious, so it is necessary to control the concentration of heavy rare earth during the diffusion process. In the present invention, the inventors have found that by alternately arranging M layers and RH layers and arranging at least one M layer between the billet and the RH layer, the heavy rare earth concentration of RH can be adjusted. In addition, in the present invention, the melting points of the M powders are all above 1000°C and do not melt or undergo other chemical reactions during the diffusion heat treatment process, so that the M layer forms a concentration adjustment layer between the RH layer and the billet, and the heavy rare earth elements in the RH layer at high temperatures can be adjusted in concentration by the M layer. The inventors have found that the particle size distribution of the M powder is an important factor for adjusting the concentration, and that if the powder particle size is too large, it will corrode the billet and pits will form on the surface of the magnet, while if the powder particle size is too small, the formed powder will be too dense and the concentration of the heavy rare earth elements will be too low, making it difficult to effectively adjust the concentration of the heavy rare earth elements. At the same time, if it is too large, the concentration of the heavy rare earth will be too small; if it is too small, it will not be able to adjust the concentration of the heavy rare earth; for the diffusion treatment of large-sized magnets, the diffusion thickness is too large, so that the heavy rare earth elements need to form a relatively stable distribution path at the magnet grain boundaries; if the diffusion concentration is too large, it will form an enrichment of heavy rare earth on the magnet surface layer, blocking the diffusion of heavy rare earth into the magnet interior; if the diffusion concentration is too small, the diffusion power will be insufficient, and the diffusion insulation time will be significantly increased, resulting in increased production costs; when the powder in the M layer meets the conditions of the present invention, the effect of the diffusion heat treatment is most excellent.Furthermore, the inventors also found that the neodymium and praseodymium on the grain boundary are very active chemically, and the neodymium and praseodymium on the grain boundary of the magnet surface are easily substituted with oxygen, and oxygen element is taken into the grain boundary. When the content of impurities such as oxygen element in the grain boundary increases, the molten state is destroyed and the wettability of the diffusion path is reduced, and the uniformity of the coercive force on the surface and inside of the diffusion magnet is reduced. If the thickness of the diffusion magnet is not large, it can be compensated for by appropriately extending the diffusion time, but if the thickness of the magnet in the diffusion direction is more than 10 mm, the smoothness of the diffusion path due to the oxygen element entering the grain boundary is greatly impaired, and the uniformity of the coercive force on the magnet surface and inside is impaired, and the improvement of the uniformity by extending the diffusion time is slight, and the manufacturing cost is greatly increased. Therefore, in the present invention, the content of oxygen element in M ​​powder is 3% or less, preferably 1% or less.

[0032] According to an embodiment of the present invention, in step (3), the diffusion heat treatment includes at least a DW heat treatment and a ST heat treatment.

[0033] According to an embodiment of the present invention, the conditions of the DW heat treatment specifically include heating to the DW temperature and then maintaining the temperature for a certain period of time. Preferably, the DW temperature is 280°C to 480°C, more preferably 320°C to 400°C. Preferably, the DW heat treatment time is 2 hours or more, for example, 3 hours, 5 hours, or 10 hours. The inventors have found that in the DW heat treatment process, most of the organic solids and solvents in the diffusion area are desorbed, and the melting points of the powders in the M layer are both 1000°C or higher, so that after the organic solids and solvents are desorbed, the M powder comes into direct contact with the billet, that is, the M layer forms a powder-like concentration adjustment layer.

[0034] In an embodiment of the present invention, the DW heat treatment is performed under vacuum conditions.

[0035] According to an embodiment of the present invention, in step (3), the ST heat treatment includes a low-temperature heat treatment and a high-temperature heat treatment, in which the temperature of the low-temperature heat treatment is 750°C to 890°C (e.g., 830°C), the temperature of the high-temperature heat treatment is 830°C to 970°C (e.g., 870°C, 890°C), the difference between the low-temperature heat treatment temperature and the high-temperature heat treatment temperature is more than 30°C, and the time of the low-temperature heat treatment and / or the high-temperature heat treatment is 50 h or less, in which the warming time is ≧2 h. Preferably, the temperature rise rate from the low-temperature heat treatment to the high-temperature heat treatment is 4 to 10°C / min, for example 5°C / min.

[0036] Preferably, the low-temperature heat treatment includes heating to a temperature for the low-temperature heat treatment and then maintaining the temperature for a certain period of time. Preferably, the high-temperature heat treatment includes heating to a temperature for the high-temperature heat treatment and then maintaining the temperature for a certain period of time. Preferably, the heating rate in the low-temperature heat treatment and the high-temperature heat treatment is not specifically limited, but is, for example, 4 to 10° C. / min, e.g., 5° C. / min.

[0037] According to a preferred embodiment of the present invention, in step (3), the ST heat treatment includes alternating low-temperature and high-temperature heat treatments.

[0038] According to an embodiment of the present invention, the time of the ST heat treatment is 2 hours or more, for example, 3 hours, 5 hours, or 10 hours.

[0039] According to an embodiment of the present invention, the ST heat treatment is performed in a vacuum state or under an inert gas, for example, the inert gas is selected from nitrogen gas, argon gas, etc.

[0040] According to an exemplary embodiment of the present invention, in step (3), the ST heat treatment includes a first heating stage, a first heat-holding heat treatment, a second heating stage, and a second heat-holding heat treatment, in which the first heating stage includes heating from 400° C. to 790° C. over 70 min, the first heat-holding heat treatment includes maintaining at 790° C. for 480 min, the second heating stage includes heating from 790° C. to 940° C. over 30 min, and the second heat-holding heat treatment includes maintaining at 940° C. for 720 min.

[0041] According to an exemplary embodiment of the present invention, in step (3), the ST heat treatment includes a first heating stage, a first temperature-retaining heat treatment, a second heating stage, a second temperature-retaining heat treatment, a third heating stage, and a third temperature-retaining heat treatment, in which the first heating stage includes heating from 420°C to 750°C over 70 min, and the first temperature-retaining heat treatment includes maintaining at 750°C for 300 min, the second heating stage includes heating from 750°C to 810°C over 30 min, and the second temperature-retaining heat treatment includes maintaining at 810°C for 420 min, the third heating stage includes heating from 780°C to 870°C over 40 min, and the third temperature-retaining heat treatment includes maintaining at 870°C for 900 min.

[0042] In the prior art, a single heat-retention temperature is generally used in the diffusion heat treatment of large-sized sintered magnets (thickness in the orientation direction ≧10 mm). The temperature range is basically between 870°C and 970°C. Different temperatures provide different diffusion forces. As a result, the conventional method for dealing with an increase in product thickness is to increase the diffusion temperature to enhance the diffusion force and thus achieve deeper diffusion of the heavy rare earth elements. However, when the diffusion thickness (i.e., orientation thickness) reaches 10 mm or more, the heavy rare earth elements are easily supersaturated on the magnet surface due to direct contact between the magnet and the heavy rare earth elements, which makes it easier for the heavy rare earth elements to penetrate into the main phase of the crystal grains, while a heavy rare earth layer is formed on the magnet surface, which may prevent subsequent diffusion of the heavy rare earth elements. The present invention realizes the adjustment control of the heavy rare earth element by increasing the M layer, and improves the above problem, but at the same time, the inventors also found that the low-temperature and high-temperature alternating heat treatment and heat retention process in the ST heat treatment process has obvious improvement in diffusion depth, and especially when the above ST heat treatment conditions of the present invention are adopted, the diffusion effect is better. This is because, in the low-temperature heat treatment diffusion process, if the heat retention temperature is lower than 750°C, the heavy rare earth RH arranged on the magnet surface cannot diffuse effectively because the temperature is too low, and if it is higher than 890°C, the diffusion efficiency is too high, and the heavy rare earth and Nd cannot be sufficiently substituted at the crystal grain boundary, so that the heavy rare earth is enriched on the magnet surface, thereby reducing the RH diffusion depth. On the other hand, in the high-temperature heat treatment diffusion process, if the heat retention temperature is higher than 970°C, the temperature is too high, and the heavy rare earth arranged on the surface directly enters the main phase, and the effect of grain boundary diffusion cannot be achieved.

[0043] According to an embodiment of the present invention, it is necessary to perform rapid cooling after the ST heat treatment, and the rapid cooling can be performed by a method known in the art, for example, a vacuum cooling method with no heating power output.

[0044] According to an embodiment of the present invention, before the diffusion portion is placed, the billet may be washed with an acid solution, deionized water, and dried. The acid solution may be selected from any acid solution known in the art, such as an aqueous hydrogen chloride solution, an aqueous nitric acid solution, etc.

[0045] According to an embodiment of the present invention, the manufacturing method further includes (4) performing an aging heat-holding treatment after the quenching and cooling, the conditions of the aging heat-holding treatment being that the aging heat-holding temperature is between 430°C and 650°C, the aging heat-holding time is longer than 30 minutes, and quenching to room temperature after the aging heat-holding is completed.

[0046] According to an embodiment of the present invention, the aging heat treatment is carried out in a vacuum or inert gas atmosphere.

[0047] The present invention further provides applications of the above R-Fe-B sintered magnets in the fields of wind power generation, household motors, automobiles, medical equipment, or mobile communication electrical equipment, and is preferably applied in the field of wind power generation.

[0048] (Beneficial Effects) (1) The present invention provides a large-sized R-Fe-B sintered magnet and a manufacturing method thereof, and solves the problems, compared to the conventional grain boundary diffusion method, that the current large-sized sintered magnets are too thick, making it difficult for heavy rare earths to diffuse into the magnet, resulting in a large difference in coercivity between the magnet surface and the magnet's interior after the diffusion process, as well as a large consumption of heavy rare earths due to diffusion and a long diffusion period.

[0049] (2) The present invention arranges a diffusion part including an M layer and an RH layer on the surface of a magnet billet, and through diffusion heat treatment including DW heat treatment and ST heat treatment, a concentration adjustment layer is formed after the organic solids and solvents in the diffusion layer are desorbed during the DW heat treatment process, thereby adjusting the heavy rare earth concentration of RH, and during the ST heat treatment process, the heavy rare earth elements in the RH layer can first pass through the powder in the M layer to reach the magnet surface, and the existence of the M layer prevents the heavy rare earth from coming into direct contact with the magnet, preventing the problem of the heavy rare earth concentration on the magnet surface being too high and accumulating at the grain boundaries to clog the diffusion path, and the concentration is adjusted and controlled after the heavy rare earth passes through the M layer during the diffusion process, preventing the occurrence of excessive concentration due to a relatively large amount of heavy rare earth arranged on the magnet surface at the beginning of diffusion. The present invention realizes the diffusion heat treatment of big-sized sintered magnets by combining the optimization of the diffusion part structure and the diffusion heat treatment process, and the internal coercivity of the obtained sintered magnets is more uniform. [Brief description of the drawings]

[0050] [Figure 1] FIG. 13 is a diagram showing the state of the diffusion portion after undergoing DW during a heat treatment process. [Diagram 2] 1 is a schematic diagram of sample collection positions of the sintered magnet in Example 1. Unit of illustration: mm. (Mode for carrying out the invention) The technical solution of the present invention will be described in more detail below in conjunction with specific examples. It should be understood that the following examples are merely for illustrative purposes and interpretation of the present invention, and should not be interpreted as limiting the scope of the claims of the present invention. Any technology realized based on the above content of the present invention is included within the scope of the claims of the present invention.

[0051] Unless otherwise specified, all materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0052] Example 1 The manufacturing method of big size sintered magnet is as follows: (1) Neodymium-iron-boron magnet (R-Fe-B magnet) was prepared, and raw materials were arranged with the target composition, specifically, Nd: 29.1%, Dy: 1.2%, Co: 1.5%, Al: 0.2%, Ga: 0.1%, Ti: 0.2%, Cu: 0.17%, B: 0.98%, and the remainder was Fe. The raw materials were melted in a melting furnace by a melt spinning casting process to obtain a neodymium-iron-boron alloy sheet, the thickness of the alloy sheet was within the range of 0.1 to 0.5 mm, the alloy sheet was coarsely crushed by a hydrogen embrittlement process to obtain powder, and the powder was further crushed by a jet mill to obtain fine powder with an SMD of 2.85 μm. The fine powder was magnetically oriented, and then press-molded to obtain a green compact density of 3.98 g / cm3. The green compact was then sintered and aged in a sintering furnace to obtain an element body. After processing the blank, the billet was prepared. The surface of the billet was washed with a nitric acid solution and deionized water, and then dried to obtain a neodymium-iron-boron billet A1. The dimensions of the billet A1 were 80 mm × 40 mm × 11 mm, the dimensional tolerance was ±0.03 mm, and the thickness Z along the orientation direction of the billet A1 was 11 mm.

[0053] (2) Arrangement of the diffusion section: The diffusion sections are arranged on the two surfaces of the billet A1 in the orientation direction, and the diffusion section has a two-layer structure, including an M layer and an RH layer, of which the M layer is in direct contact with the surface of the billet A1, and the RH layer is arranged on the surface of the M layer. The specific process is as follows:

[0054] (a) The manufacturing process of the M layer includes preparing a first slurry using graphite powder (oxygen content in the powder is 0.07%), organic solid rosin modified alkyd resin, and ethanol, in which the weight percentages of graphite powder, organic solid rosin modified alkyd resin, and ethanol are 55 wt%, 2 wt%, and 43 wt%, respectively; the first slurry is applied to the surface of the billet A1 by spraying, and then dried with hot air at 60°C. After drying, an M layer is obtained, the thickness of which is 3±2 μm.

[0055] (b) Then, an RH layer is arranged on the surface of the M layer after drying, and the manufacturing process of the RH layer includes preparing a second slurry using terbium hydride powder, organic solid rosin modified alkyd resin, and ethanol, in which the weight percentages of the terbium hydride powder, organic solid rosin modified alkyd resin, and ethanol are 62 wt%, 3 wt%, and 35 wt%, respectively, and similarly, the second slurry is arranged on the surface of the M layer by spraying, and after the spray coating is completed, it is again dried with hot air at 60°C, and after drying, an RH layer is obtained, and its thickness is 50±15 μm. That is, after the arrangement of the surface diffusion part of the billet A1 is completed, the billet A2 is formed.

[0056] (3) Diffusion heat treatment: The billet A2 is placed in a graphite case and subjected to diffusion heat treatment. The diffusion heat treatment process starts with heating in a vacuum state, with a vacuum degree of ≦10 Pa. The diffusion heat treatment process mainly includes heating, DW, ST and cooling processes. The specific diffusion heat treatment process is as follows: 1) Temperature increase: The temperature was increased to 400°C over 80 min; 2) DW: maintained at 400℃ for 240 min; 3) Temperature increase: The temperature was increased from 400°C to 850°C over 70 min; 4) ST1: maintained at 850℃ for 480 min; 5) Temperature increase: The temperature was increased from 850°C to 940°C over 30 min; 6) ST2: maintained at 940℃ for 1080 min; (4) Aging treatment: after the diffusion heat treatment is completed, fill with argon gas, start the fan to rapidly cool to below 80°C, and after the rapid cooling is completed, heat up to 500°C for aging treatment (heating rate is 5°C / min, and the heat retention time is 120 min. Aging treatment refers to a heat treatment process in which the alloy workpiece is left at a relatively high temperature after solid solution treatment, cold plastic deformation or casting or forging, or at room temperature to retain its performance, shape and dimensions and change over time). After the aging treatment is completed, fill with argon gas again, start the fan to rapidly cool to 80°C, and obtain the final NdFeB sintered magnet A3.

[0057] FIG. 1 shows the state of the diffusion zone after DW in the heat treatment process. After the DW process, the organic solids and solvents in the M layer escape from the diffusion zone. At this time, the M layer of the diffusion zone is mainly graphite powder, and the RH layer is mainly terbium hydride powder.

[0058] (5) The neodymium-iron-boron sintered magnet A3 was inspected as follows.

[0059] 1) Sampling: As shown in Figure 2, a neodymium iron boron sintered magnet A3 was cut along its orientation direction to obtain a diffusion cross-sectional area. Samples measuring 1 mm x 1 mm x 1 mm were taken at the surface of the sintered magnet in the diffusion cross-sectional area and at a position 5 mm away from the surface, and named H1-1 and H1-2, respectively.

[0060] The performance of samples H1-1 and H1-2 of Example 1 was measured and compared. The measurement results are shown in Table 1.

[0061] 2) The measurement conditions are as follows: Sample size: 1mm×1mm×1mm, tolerance ±0.03mm; Test temperature: 23℃ Inspection equipment: UK HIRST PFM06 (maximum coercive force of 60 kOe can be measured, temperature range: 16~40℃, minimum inspection possible for B1×1×1 sample).

[0062] [Table 1]

[0063] Example 2 The manufacturing method of big size sintered magnet is as follows: (1) A neodymium-iron-boron magnet (R-Fe-B magnet) was prepared, and raw materials were arranged with the target composition, specifically, PrNd: 28.6%, Dy: 1.5%, Co: 1.0%, Al: 0.1%, Ga: 0.2%, Ti: 0.12%, Cu: 0.10%, B: 0.98%, and the remainder was Fe. The raw materials were melted in a melting furnace by a melt spinning casting process to obtain a neodymium-iron-boron alloy sheet, the thickness of the alloy sheet was within the range of 0.1 to 0.5 mm, the alloy sheet was coarsely crushed by a hydrogen embrittlement process to obtain powder, and the powder was further crushed by a jet mill to obtain fine powder with an SMD of 2.85 μm. The fine powder was subjected to magnetic field orientation, and then press-molded to obtain a green compact density of 3.95 g / cm3. The green compact was then sintered and aged in a sintering furnace to obtain an element body. After processing, the billet was washed with a nitric acid solution and deionized water, and then dried to obtain a neodymium iron boron billet B1. The dimensions of the billet B1 were 100 mm × 50 mm × 15 mm, the dimensional tolerance was ±0.03 mm, and the thickness Z in the orientation direction of the billet A1 was 15 mm.

[0064] (2) Arrangement of the diffusion section: The diffusion section is arranged on the surface of the billet B1, and the diffusion section has a four-layer structure, which is, from the surface of the billet B1, the M1 layer, the RH1 layer, the M2 layer, and the RH2 layer, in that order, of which the first M1 layer is in direct contact with the billet B1. The specific process is as follows:

[0065] (a) The manufacturing process of the M1 layer includes preparing a first slurry using molybdenum powder (oxygen content in the powder is 0.65%), organic solid polyvinyl butyral, and ethanol, in which the weight percentages of the molybdenum powder, organic solid polyvinyl butyral, and ethanol are 60 wt%, 5 wt%, and 35 wt%, respectively; the first slurry is applied to the surface of the billet B1 by spraying, and then dried with hot air at 60°C. After drying, an M1 layer is obtained, the thickness of which is 3±2 μm.

[0066] (b) After drying, an RH1 layer is disposed on the surface of the M1 layer. The manufacturing process of the RH1 layer includes preparing a second slurry using dysprosium hydride powder, organic solid polyvinyl butyral, and ethanol, in which the weight percentages of the dysprosium hydride powder, organic solid polyvinyl butyral, and ethanol are 60 wt%, 8 wt%, and 32 wt%, respectively. Similarly, the second slurry is disposed on the surface of the M1 layer by spraying. After the spray coating is completed, a drying process is again performed with hot air at 60°C. After drying, an RH2 layer is obtained, and its thickness is 40±15 μm.

[0067] (c) After the drying is completed, the above steps (a) and (b) are repeated to sequentially arrange one M2 layer and one RH2 layer, which are respectively prepared by using the first slurry and the second slurry in steps (a) and (b). After drying, the thickness of the M2 layer is 2±1 μm, and after drying, the thickness of the RH2 layer is 35±15 μm. After the arrangement of the surface diffusion portion of the billet body B1 is completed, a billet B2 is formed.

[0068] (3) Diffusion heat treatment: The billet B2 is placed in a graphite case and subjected to diffusion heat treatment. The diffusion heat treatment process starts with heating in a vacuum state, with a vacuum degree of ≦10 Pa. The diffusion heat treatment process mainly includes heating, DW, ST and cooling processes. The diffusion heat treatment process is specifically as follows: 1) Temperature increase: The temperature was increased from 50°C to 420°C over 80 min; 2) DW: maintained at 420℃ for 240 min; 3) Temperature increase: The temperature was increased from 420°C to 750°C over 70 min; 4) ST1: maintained at 750℃ for 300 min; 5) Temperature increase: The temperature was increased from 750°C to 810°C over 30 min; 6) ST2: maintained at 810℃ for 420 min; 7) Temperature increase: The temperature increased from 780°C to 870°C over 40 min; 8) ST3: maintained at 870℃ for 1200 min; (4) Aging treatment: After the diffusion heat treatment is completed, fill with argon gas, start the blower to rapidly cool to below 80°C, and after the rapid cooling is completed, heat up to 520°C and perform aging treatment (heating rate is 5°C / min, and the heat retention time is 300 min. Aging treatment refers to a heat treatment process in which the alloy workpiece is left at a relatively high temperature after solid solution treatment, cold plastic deformation or casting or forging, or at room temperature to retain its performance, shape, and dimensions and change over time). After the aging treatment is completed, fill with argon gas again, start the blower to rapidly cool to 80°C, and obtain the final NdFeB sintered magnet B3.

[0069] (5) The neodymium-iron-boron sintered magnet B3 of this example was inspected with reference to Example 1, with the difference being that A3 was replaced with B3, and the samples were named H2-1 and H2-2, respectively. The measurement results are shown in Table 2.

[0070] [Table 2]

[0071] Comparative Example 1 In this comparative example, a billet was manufactured using the same sample manufacturing process as in Example 1, with the following differences.

[0072] (2) Diffusion sections were arranged: Diffusion sections were arranged on two surfaces in the orientation direction of the billet A1, and an RH layer was directly arranged on the diffusion sections. The manufacturing process of the RH layer included preparing a slurry using terbium hydride powder, organic solid rosin-modified alkyd resin, and ethanol, in which the weight percentages of terbium hydride powder, organic solid rosin-modified alkyd resin, and ethanol were 62 wt%, 3 wt%, and 35 wt%, respectively. Similarly, the slurry was directly arranged on the surface of the billet A1 by spraying. After the spray coating was completed, a drying treatment was again performed with hot air at 60°C. After drying, an RH layer was obtained, and its thickness was 50±15 μm.

[0073] The other steps (1), (3) and (4) were the same as in Example 1, and in this comparative example, a neodymium-iron-boron sintered magnet C3 was finally obtained.

[0074] (5) Neodymium-iron-boron sintered magnet C3 was inspected with reference to Example 1, with the difference being that A3 was replaced with C3, to obtain samples D3-1 and D3-2 of Comparative Example 1.

[0075] [Table 3]

[0076] Comparative Example 2 In this comparative example, a billet was manufactured using the same sample manufacturing process as in Example 2, with the following differences.

[0077] (2) A diffusion portion was provided: the oxygen element content in the molybdenum powder used in the M layer was 5.5%, and the oxygen element content in the molybdenum powder used in Example 2 was 0.65%.

[0078] The other steps (1), (2), and (4) were the same as in Example 2, and this comparative example ultimately produced a neodymium-iron-boron sintered magnet D4, and samples D4-1 and D4-2 of Comparative Example 2. The results showed that the performance of the entire sample had deteriorated, and the uniformity of the coercive force had deteriorated.

[0079] [Table 4]

[0080] Comparative Example 3 This comparative example is basically the same as Example 2, except that the diffusion heat treatment process in step (3) is specifically as follows: 1) Temperature increase: The temperature was increased from 50°C to 420°C over 80 min; 2) DW: maintained at 420℃ for 240 min; 3) Temperature increase: The temperature increased from 420°C to 870°C over 140 min; 4) ST: Maintained at 870℃ for 900 min.

[0081] The other steps (1), (2) and (4) were the same as in Example 1, and in this comparative example, a neodymium-iron-boron based sintered magnet E5 was finally obtained.

[0082] (5) The neodymium-iron-boron sintered magnet E5 of this example was inspected with reference to Example 1, with the difference being that A3 was replaced with E5, and the samples were named E5-1 and E5-2, respectively. The measurement results are shown in Table 5.

[0083] [Table 5]

[0084] The exemplary embodiments of the present invention have been described above. However, the scope of the claims of the present application is not limited to the above embodiments. Any modifications, equivalent replacements, improvements, etc. made by those skilled in the art without departing from the spirit and principles of the present invention should be included in the scope of the claims of the present invention.

Claims

1. 1. A sintered R-Fe-B magnet, characterized in that a thickness of the sintered R-Fe-B magnet in an orientation direction is 10 mm or more, any one cross section along the orientation direction is a diffusion cross-sectional region, a side of the diffusion cross-sectional region closer to an outer surface of the sintered R-Fe-B magnet is a diffusion cross-sectional region surface, and a difference in coercivity between the diffusion cross-sectional region surface and a point 5 mm away from the diffusion cross-sectional region surface is ΔH, and ΔH≦50 kA / m.

2. △H is 45 kA / m or less, Preferably, the thickness in the direction of orientation is between 10 mm and 20 mm; Preferably, the raw materials for the R-Fe-B sintered magnet include R, B, Fe and M, among which: the mass content of R is 27 to 34 wt%, preferably 29 to 32 wt%, the mass content of M is 0 to 5 wt%, preferably 0 to 3 wt%, Preferably, R is at least one selected from the rare earth elements Nd, Pr, Tb, Dy, Gd, Ho, The R-Fe-B sintered magnet according to claim 1, characterized in that M is preferably at least one selected from Ti, V, Cr, Mn, Co, Ga, Cu, Si, Al, Zr, Nb, W, and Mo.

3. A method for producing the R-Fe-B sintered magnet according to claim 1 or 2, comprising the steps of: (1) preparing a billet of R-Fe-B magnet having a thickness of ≥ 10 mm; (2) Arranging a diffusion section: arranging a diffusion section on at least two surfaces in the orientation direction of the billet obtained in step (1), the diffusion section including at least one RH layer and one M layer, the M layer being in direct contact with the billet surface, and at least one M layer being spaced between the RH layer and the billet; (3) Diffusion Heat Treatment: A method for producing a sintered R-Fe-B magnet, comprising the steps of: subjecting the billet on which the diffusion layer is disposed in step (2) to a diffusion heat treatment to obtain the sintered R-Fe-B magnet.

4. In step (2), the diffusion section has RH layers and M layers alternately arranged, and at least one M layer is separated between the RH layer and the billet, the RH layers include 1 to 3 layers, and the M layers include 1 to 3 layers; Exemplarily, the diffusion section includes one M layer and one RH layer, Exemplarily, the diffusion portion includes two M layers and two RH layers, which are arranged in the order of a first M layer, a first RH layer, a second M layer, and a second RH layer from the surface of the billet. Preferably, the first M layer and the second M layer may be either homogeneous or different. Preferably, the first RH layer and the second RH layer may be either homogeneous or different. The method according to claim 3, characterized in that, preferably, in the diffusion portion, the thickness of each RH layer is 1 μm to 70 μm.

5. The manufacturing method of the RH layer specifically includes disposing an RH slurry on two surfaces of the billet in the orientation direction, and then drying the RH layer; Preferably, the RH slurry comprises a heavy rare earth element, an organic solid, and a solvent; Preferably, in the RH slurry, the mass ratio of heavy rare earth element, organic solid, and solvent is (40-70):(0.5-12):(0-50); Preferably, the heavy rare earth element includes at least one of metallic dysprosium, metallic terbium, dysprosium hydride, terbium hydride, dysprosium fluoride, terbium fluoride, dysprosium oxide, and terbium oxide; Preferably, the organic solid is at least one selected from a rosin-modified alkyd resin, a thermoplastic phenolic resin, a urea resin, and polyvinyl butyral; Preferably, the solvent is at least one selected from an alcohol solvent, an ether solvent, and an aromatic hydrocarbon solvent; Preferably, in the diffusion section, the thickness of each M layer is less than 20 μm and more than 0.1 μm, preferably less than 10 μm; 5. The method according to claim 3, wherein the ratio of the thickness of each RH layer to the thickness of each M layer in the diffusion section is preferably (1-70):(0.1-20).

6. The manufacturing method of the M layer specifically includes disposing a slurry containing M powder on two surfaces in the orientation direction of the billet, and then drying the slurry to obtain the M layer; Preferably, the M powder-containing slurry contains M powder, an organic solid, and a solvent, Preferably, in the M powder-containing slurry, the mass ratio of M powder, organic solid, and solvent is (20-70):(1-10):(0-50); Preferably, the M powder includes at least one of graphite powder, titanium powder, zirconium powder, molybdenum powder, tungsten powder, titanium oxide, zirconium oxide, molybdenum oxide, and tungsten oxide, and the content of oxygen element in the M powder is less than 3%, preferably less than 1%; A method according to any one of claims 3 to 5, characterized in that the M powder preferably comprises powders with a grain size of less than 5 μm, and the powders with a grain size between 0.5 μm and 1.8 μm account for more than 50% of the total powder mass, preferably more than 65%.

7. In step (3), the diffusion heat treatment includes at least a DW heat treatment and a ST heat treatment; Preferably, the conditions of the DW heat treatment specifically include heating to the DW temperature and then maintaining the temperature for a certain period of time, preferably the temperature of the DW is 280°C to 480°C, more preferably 320°C to 400°C, and preferably the time of the DW heat treatment is 2 hours or more; The method according to any one of claims 3 to 6, characterized in that the DW heat treatment is preferably carried out under vacuum conditions.

8. In step (3), the ST heat treatment includes a low-temperature heat treatment and a high-temperature heat treatment, in which the temperature of the low-temperature heat treatment is 750°C-890°C, the temperature of the high-temperature heat treatment is 830°C-970°C, the difference between the low-temperature heat treatment temperature and the high-temperature heat treatment temperature is more than 30°C, and the time of the low-temperature heat treatment and / or the high-temperature heat treatment is not more than 50 h, in which the heat retention time is ≥ 2 h, and preferably, the heating rate from the low-temperature heat treatment to the high-temperature heat treatment is 4-10°C / min; Preferably, the low-temperature heat treatment includes increasing the temperature to a low-temperature heat treatment temperature and then maintaining the temperature for a certain period of time, and preferably, the high-temperature heat treatment includes increasing the temperature to a high-temperature heat treatment temperature and then maintaining the temperature for a certain period of time, Preferably, in step (3), the ST heat treatment includes alternating low-temperature and high-temperature heat treatments, Preferably, the time of the ST heat treatment is 2 hours or more in each case, The method according to any one of claims 3 to 7, characterized in that the ST heat treatment is preferably carried out in a vacuum state or under an inert gas.

9. Before disposing the diffusion portion, the billet may be washed with an acid solution and deionized water, and then dried. Preferably, the manufacturing method further includes (4) performing an aging heat-retention treatment after the quenching and cooling, the conditions of the aging heat-retention treatment being that the aging heat-retention temperature is between 430 and 650°C, the aging heat-retention time is longer than 30 minutes, and the aging heat-retention is followed by quenching to room temperature after the aging heat-retention; The method according to any one of claims 3 to 8, characterized in that the aging heat treatment is preferably carried out in a vacuum or inert gas atmosphere.

10. The application of the R-Fe-B sintered magnet according to claim 1 or 2 in the fields of wind power generation, domestic motors, automobiles, medical equipment, or mobile communication electrical equipment, preferably in the field of wind power generation.

Citation Information

Patent Citations

  • Grain boundary diffusion method for preparing high-performance special-shaped neodymium-iron-boron magnet

    CN115116728A

  • R-Fe-B-BASED RARE-EARTH SINTERED MAGNET AND METHOD FOR PRODUCING THE SAME

    JP2011223007A

  • R-t-b based sintered magnet and motor

    JP2017055074A

  • Method for manufacturing r-t-b based permanent magnet

    JP2020167209A

  • Production method for r-t-b-based sintered magnet

    WO2016093173A1